SWOT Analysis of The Potential for Cash Waqf in Indonesia: NVivo Approach and Literature Review - Doni Yusuf Bagaskara; Rohmadi (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aims to determine the SWOT analysis of the Potential of Cash Waqf in Indonesia using the NVivo approach. This research uses qualitative methodology with the NVivo approach and literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on SWOT analysis regarding "Cash Waqf" using NVivo 14 software; (2) map the visualization results with a hierarchical diagram and test the correlation between media articles using SWOT analysis; (3) mapping research topics with Worldcloud or a collection of words that are often discussed in media articles; and (4) Testing the significant value between media articles to determine the size or size of the correlation around the topic "Cash Waqf". The results of this research show that the topics often discussed in media articles regarding Cash Waqf in Indonesia are threats and strength. Meanwhile, a topic that is rarely discussed by media articles regarding Cash Waqf in Indonesia is opportunities and weaknesses. The implications of this research show that the resulting SWOT study and Literature Review provide recommendations for increasing the potential of Cash Waqf in Indonesia in the future.